Effects of whole-body vibration training combined with KAATSU training on lower limb joint muscle strength in older women - Xiong, Weizhi; Liu, Xuefeng (Frontiers in Physiology, 2023)
Objective: This study aimed to investigate the effect of whole-body vibration training (WBVT) combined with KAATSU training (KT) on lower limb joint muscle strength and to provide a reference for improving muscle strength in older women.: A total of 86 healthy older people was randomly divided into WBVT group (WG, n = 21), KT group (KG, n = 22), combined intervention group (CIG, n = 20) and control group (CG, n = 23). WG and CIG subjects underwent WBVT, and KG and CIG subjects underwent 150 mmHg and lower limb joint and local compression intervention for 16 weeks (three times per week, about 15 min/time).Results: 1) Results at 16 weeks were compared with the baseline data. The knee extension and ankle flexion PT (60°/s) in CIG increased by 14.3 and 15.3%, respectively (P<0.05). The knee extension PT (180°/s) increased by 16.9, 18.4 and 33.3% in WG, KG and CIG (P<0.05), respectively, and the ankle extension PT (180°/s) in CIG increased by 31.1% (P<0.05). The hip, knee extension and ankle flexion ER increased by 10.0, 10.9 and 5.7% in CIG (P<0.05), respectively. 2) Results were compared among groups at 16 weeks. The relative changes were significantly lower in WG, KG and CG compared to CIG in the knee extension and ankle flexion PT (60°/s) (P < 0.05). The relative changes were significantly greater in WG, KG and CIG compared to CG in the knee extension PT (180°/s) (P < 0.05). The relative changes were significantly lower in WG, KG and CG compared to CIG in the ankle extension PT (180°/s) (P < 0.05). The relative changes were significantly lower in WG, KG and CG compared to CIG in the hip extension ER (P < 0.05). and lower in CG compared to CIG in the knee extension ER (P < 0.05).Sixteen-week WBVT and KT increased the knee extensor strength in older women. Compared with a single intervention, the combined intervention had better improvements in the knee extensor and ankle flexor and extensor strength and hip extension muscle endurance. Appears to be some additional benefit from combined intervention above those derived from single-interventions.